Improved peridynamics approach for the progressive fracture of marine concrete. (1st July 2022) - Li, Shuang; Lu, Haining; Huang, Xiaohua; Yang, Jianmin
Abstract: Crack initiation and propagation in marine concrete play a significant role in the security and durability of concrete in ocean construction. Peridynamics (PD), which reformulates classical continuum mechanics in terms of spatial integral equations instead of partial differential equations, has been used successfully to match the fracture patterns observed in experiments. However, the classical bond-based peridynamics (BPD) describe brittle fracture instead of quasi-brittle fracture; this includes the failure of quasi-brittle solid marine concrete. Further, the models have significant surface effects, and the effect of the internal length on nonlocal long-range forces is not reflected. The current work proposes an improved BPD approach to overcome the three drawbacks of fracture analyses of marine concrete. A novel kernel function is incorporated, an effective PD surface effect correction method is used, and the BPD bond stiffness at the boundary is modified. Then, the constitutive force function of the BPD is established based on the linear and nonlinear mechanical behaviours of the progressive fracture of ocean concrete materials, and a corresponding failure criterion is given. The validity and accuracy of the proposed method are demonstrated via numerical analyses and experiments. The proposed method can fully capture the nonlinear deformation and progressive fracture of marine concrete. Highlights: The bond-based peridynamics (BPD) constitutive force functions are reconstruction. An effective PD surface effect correction method is considered. The ability of a novel kernal function to enhance accuracy of BPD is proved. Improved peridynamics approach is proposed for fracture analyses of marine concrete. The seepage path of seawater can be predicted by fully capturing the crack progression of ocean engineering concrete.